Implementasi Pendidikan Karakter di Pondok Pesantren - Nafsan Nafsan; Alfurqan Alfurqan (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to determine the method of character education at the Islamic Boarding School of Madrasah Tarbiyah (MTI) Tabek Gadang, Guguak District. This study uses a qualitative method with the type of research field research (field research). Sources of research data are the head of the Islamic boarding school, Ustadz/Ustadzah, dormitory supervisors, and several students. Data collection techniques used in this study were observation, in-depth interviews, and documentation. The research data was tested for validity using triangulation and persistence techniques. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that the values ​​of character education that are instilled are in the form of character towards God Almighty, oneself, others, the environment, and the nation by using exemplary methods, habituation, advice, and stories.